The sexual victimization of college students: a test of routine activity theory - Hayes, Brittany E. (Crime & delinquency, 2021)
This study examines the applicability of theoretically-relevant routine activity variables to understand the risk of sexual victimization among college students. Analyses assess if routine activity-related variables have similar explanatory power for rape and sexual assault. Indicators of “proximity to motivated offenders” and “exposure to crime” were associated with rape. Indicators related to “proximity to motivated offenders,” “exposure to crime,” and “target attractiveness” were associated with sexual assault. Indicators capturing “guardianship” were not associated with either rape or sexual assault. Theoretical implications and directions for future research are discussed. Specifically, it is possible to theory-test using campus climate survey instruments.